The Influence Of Regional Original Income And Economic Growth On Capital Expenditure In Indonesia During The Digital Era - Harini Vita Puteri; Putri Wahyuni; Frenky Situmorang (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2023)
The objective of this research’s to understand and analyze Regional Original Income and Economic Growth significantly affect the Capital Expenditure in Indonesia during the Digital Era. This study uses quantitative data methods and the type of data is secondary data. The population of this study includes all 34 provinces in Indonesia as of 2022. The sample in this study uses a saturated sampling technique, which means that is uses the entire population in this study. Data analysis and testing consist of descriptive statistics, classical assumption test, multiple regression analysis, partial hypothesis testing (T-test), simultaneous hypothesis testing (F test), and coefficient of determination test. The results of this study indicate that Regional Original Income has a partially significant effect on Capital Expenditure with a calculated T count of 6,570 > T-table 2,037. Economic Growth has no partial effect on Capital Expenditure with a calculated T count of 0,293 < T-table 2,037. Regional Original Income and Economic Growth simultaneously have a significant effect on Capital Expenditure with a calculated F count of 21,602 > F-table 3,30 and a regression coefficient value of 58,2%.